Analisis dampak kredit Bank Plecit pada kesejahteraan ekonomi masyarakat di sekitar Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung - Abin, Moh. Rois; Himmati, Risdiana; Alinda, Ria; Al-Mubarok, M. Ahris; Oktavia, Nevi; Umam, Ahmad Choirul (Nur Science Institute, 2024)
This study aims to identify the factors that lead the community around Sayyid Ali Rahmatullah State Islamic University Tulungagung to become entangled with Plecit Bank and the impact of Plecit Bank loans on the welfare of the surrounding community. The method used is a case study. Data collection techniques involve direct interviews in the field. This research employs non-probability sampling with purposive sampling. Purposive sampling is used in this study because it aligns with the research objectives. Based on the research, it is concluded that the practices of Plecit Bank are driven by the ease of applying for loans. Three factors influence the community around Sayyid Ali Rahmatullah State Islamic University Tulungagung in taking loans: economic, social, and psychological. Furthermore, neither informant feels assisted by Plecit Bank loans. This is due to the very high interest rates ranging from 25% to 30%, or between 250,000 to 300,000 for a loan of 1,000,000. Consequently, this situation leaves the informants in a state of insecurity and reluctance to take out loans from Plecit Bank.